The Relationship Between Water Quality and Phytoplankton Abundance with Different Showing Density in Litopenaeus vannamei Ponds in Bayeman Village, Probolinggo District, East Java - Fika Fitrianesia; Asus Maizar Suryanto Hertika; Uun Yanuhar; Muhammad Faiq Ash Shiddiq (Jurnal Penelitian Pendidikan IPA, 2024)
Intensive ponds often experience a decrease in water quality and cause ponds to bloom due to the fertility of the pond bottom due to the buildup of organic material originating from leftover feed, feces and the remains of dead shrimp. The aim of this research is to determine the relationship between water quality and phytoplankton abundance in intensive pond types with different densities in Bayeman Village, Probolinggo Regency. The research was carried out from January to March 2023. Samples were taken using the purposive sampling method in 6 different pond plots. Phytoplankton analysis was carried out at the Laboratory of the Sand Source Freshwater Fisheries Technical Implementation Unit and the Hydrobiology Laboratory of the Fish Resources Section of the Faculty of Fisheries and Marine Sciences. Measurement of in situ water quality parameters, namely temperature, pH, brightness, DO, TDS, light intensity, salinity and ex situ nitrate, phosphate and ammonia using spectrophotometric methods. The correlation test results of physico-chemical parameters related to phytoplankton abundance have a strong and heterogeneous relationship only with the orthophosphate parameter